KOMPARASI HASIL BELAJAR SISWA YANG DIAJARKAN DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DAN NUMBERED HEADS TOGETHER (NHT) - Aida, Nur; Laamena, Christina M; Molle, Juliana S (Sora Journal of Mathematics Education, 2024)
This study is motivated by the observation that most students still make mistakes in understanding and applying problems in algebraic form, and the learning process is still teacher-centered. This study aims to determine which is better between mathematics learning outcomes in MTs students taught using the Think Pair Share (TPS) cooperative learning model and the Numbered Heads Together (NHT) cooperative learning model on algebraic form material in class VII. One of the efforts that can be made to actively involve students in learning is to apply the Think TPS cooperative learning model and the NHT cooperative learning model. The type of research used is experimental research with Post Test Group Design research design. In this study, the population used was all students of class Vll consisting of 3 classes with a total of 78 students, selected using purposive sampling technique, namely class VII1 as the first experimental class taught with the TPS cooperative learning model and class VII3 as the second experimental class taught with the NHT) cooperative learning model. For each class there were 31 and 23 students, so that the total number of samples in this study was 54 people. The instrument used in this study is a test question consisting of 4 description questions. Based on the t-test statistical analysis, the Sig. (2-tailed) value of 0.006 is smaller than α = 0.05 so there is a significant difference between the two models. Furthermore, the Mean value in the Group Statitics table shows that the Mean value of Think Pair Share is 62.19 and the Mean value of Numbered Heads Together is 50.19. these results can prove that the superior learning model is the TPS Cooperative Learning Model .